Evaluation of School Health Surveillance System characteristics in Baghdad Governorate - Musa, ali; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2012)
Objectives: Evaluation of school health surveillance system with Indicate the level of usefulness of this system,in addition to Describe the system.Methodology: A probability multistage sample of (54) subjects which is selected the school health units fromthe health institutions. Questionnaire has been divided into three main parts consist, form(A) especially forhealth directorate, form (B) for health sectors, and form (C) for primary health care centers; each form containsthe basic components, structure, process, outcome, total items of questionnaire was ( 74) items.Results: The study results indicate that the system is average adequacy, simple, moderately flexible, highlyacceptance, representative, low utility and unstable system.Recommendation: The study recommended computerizing the system data as addition to manualdocumentation. Statisticians may coordinate the monthly surveillance forms. Involving all health institutions andcenters related to school health in the surveillance system program.